Teachers’ Strategy to Develop Higher Order Thinking Skills in Reading Class - Fitriani, Yesi Elsa; Syarifah, Eva Fitriani; Emiliasari, Raynesa Noor (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
This research aims to find out the strategies used by the teachers and the inhibiting factors that can influence the development of HOTS in Reading Class. It applied qualitative approach with case study research design. The subject of the research were two English teachers of Senior High School. The techniques of collecting the data were used observation and interview. The data were analyzed using the qualitative method there are data reduction, data display, and drawing conclusions. The finding of the research shows that there were 5 types of teaching strategies, including informing learning objectives, divergent questions, group discussion, giving feedback and giving motivation. The most dominant strategy used by the teacher was divergent question. Meanwhile, the learning objective and group discussion was the least prominent, with only 3 data. Then, five inhibiting process such as time, pupil learning ability, pupil’s mastery, planning domain, and class environment can influence the development of HOTS.